Study guide to accompany economics of social issues - Yoho, DeVon L.; Leftwich, Richard H; Sharp, Ansel M. (Plano, Tex. : Business Publications, 1984)
A workbook to help the user study the 'Economics of Social Issues'. It would help to systematically and effectively study the book and provides with the learning objectives, questions, and problems that will help one understand the tools of economic analysis and apply them to social issues and problems.
oif 05/03/2019
Loans
Keywords: Economics -- Sociological aspects; Economics -- Sociological aspects -- Problems, exercises, etc; Social problems--Study and teaching; Economics---Study and teaching